EVALUATION OF REPEATED DOSE-90-DAY ORAL TOXICITY STUDY OF L-DOPA AND HYOSCINE HYDRBROMIDE COMBINATION IN RATS - Attar, Sabir Husain; Khatri, Dharmendra Kumar; Sancheti, Jayant; Juvekar, Archana Ramesh (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The present study was done to evaluate repeated-dose 90-day oral toxicity studies of l-dopa and hyoscine hydrbromide combination in rats. Methods: Repeated-dose 90-day oral toxicity study was performed according to the Organisation for Economic Co-operation and DevelopmentÂ (OECD) guidelines 408. In the present study, combination of L-dopa and hyoscine hydrobromide was administered at 5 times the upper limit of therapeutic dose of each drug which is 1200 mg per day for L-dopa and 0.75 mg per day for hyoscine hydrobromide for adult human being and which was converted to required dose for Wistar rats (5 males and 5 females). Results: The combination of L-dopa and hyoscine hydrobromide at 5 times the upper therapeutic dose produced no treatment-related signs of toxicity or mortality in any of the animals tested during 90 d of the study. The subchronic administration of the combination of L-dopa and hyoscine hydrobromide did not produce any significant difference in any of the assigned parameters between the control and all treatment groups. Conclusion: It is established that the combination of L-dopa and hyoscine hydrobromide therapy is safe on repeated dose 90-day oral toxicity at 5 times the upper limit of therapeutics dose of each drug. Â